Cuerpo (en)marcado : ensayos sobre arte colombiano contemporáneo - Agudelo, Pedro Antonio, (Instituto Tecnológico Metropolitano, 2016)
This text discusses artistic practices, changes in perspective and their implications on the representation and presentation of human body, in order to expand the comprehension of the history of art in Colombia. Likewise, this text analyzes the topic of human body within the work of some of the most important artists in our country, and it reviews the relationships among human body and tradition, erotism, image, materiality, instincts and culture, in order to reshape the definition of image and the poetics of behavior, and to define the role played by culture in the artistic practices that use the human body as a central topic.